2011
DOI: 10.3892/ijo.2011.1027
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin triggers apoptosis in human osteosarcoma U-2 OS cells through the endoplasmic reticulum stress, mitochondrial dysfunction and caspase-3-dependent signaling pathways

Abstract: Abstract. Wogonin (5,7-dihydroxy-8-methoxyflavone) is a flavone constituent of Scutellaria baicalensis with various beneficial biological activities and it has been shown to have tumor therapeutic potential in vitro and in vivo. The purpose of this study was to investigate the effects of wogonin in a human osteosarcoma cell line (U-2 OS). Results showed that a dose-and time-dependent reduction occurred in cell viability after exposure to wogonin in U-2 OS cells. Increasing the levels of reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…We speculated that there must be a pathway independent of ROS and ER stress involved in LZ-205-induced apoptosis. Previous studies found that Wogonin induces apoptosis through the Fas-related extrinsic signaling pathways in human osteosarcoma U-2 OS cells [18] and human leukemia CEM T cells [31, 32]. In the present study, LZ-205 also increased Fas and FasL expression and subsequently activated caspase 8.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We speculated that there must be a pathway independent of ROS and ER stress involved in LZ-205-induced apoptosis. Previous studies found that Wogonin induces apoptosis through the Fas-related extrinsic signaling pathways in human osteosarcoma U-2 OS cells [18] and human leukemia CEM T cells [31, 32]. In the present study, LZ-205 also increased Fas and FasL expression and subsequently activated caspase 8.…”
Section: Discussionsupporting
confidence: 72%
“…Wogonin induces apoptosis in hepatocellular carcinoma cells through the caspase 3 pathway and alternative expression of p21 protein [1517] or by activating other pathways [18, 19]. In addition, many wogonin derivatives have been reported to possess potential anti-tumor properties, such as LYG-202, LW-214, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A375.S2 cells at a density of 2 × 10 5 cells/well were placed onto 6-well plates and treated with bufalin (0, 150, 250, 350, 450, and 550 nM) for 24 and 48 h before cells from each treatment were isolated for DAPI staining as described previously [31, 32]. After staining, the cells were examined and photographed using a fluorescence microscope at 200x magnification [33, 34].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested from each treatment, resuspended in 500  μ L of H 2 DCF-DA (5  μ M) for ROS (hydrogen peroxide; H 2 O 2 ) at 37°C for 30 min. Consequently, cells were immediately analyzed by flow cytometry as described elsewhere [28, 29]. All fluorescence intensities were obtained from the mean intensity of the histogram constructed from approximately 10,000 cells using BD CellQuest Pro software.…”
Section: Methodsmentioning
confidence: 99%